A new species of Scaphytopiini (Hemiptera: Cicadellidae: Deltocephalinae), with a key to genera and species checklist for the tribe from China - Xing, Ji-Chun; Dai, Ren-Huai; Li, Zi-Zhong (Zootaxa, 2011)
An annotated checklist and generic key to the leafhopper tribe Scaphytopiini from China is provided. A new species Xenovarta subulata sp. nov. is described and illustrated from China. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).